ChemInform Abstract: A Visible‐Light‐Mediated Radical Smiles Rearrangement and Its Application to the Synthesis of a Difluoro‐Substituted Spirocyclic ORL‐1 Antagonist. Issue 15 (24th March 2016) - Douglas, James J.; Albright, Haley; Sevrin, Martin J.; Cole, Kevin P.; Stephenson, Corey R. J.
Abstract: A photolytic Smiles rearrangement of sulfonic acid esters (I) to produce difluoroalkyl substituted arenes and hetarenes is described.